(untitled) (Scientific journal of the Fergana State University, 2023)
Today in modern pedagogy, there is a need to introduce acrobatics classes into the pedagogical process for the development of a comprehensively developed personality. There is an active search for innovations, but the main innovations begin with physical education lessons, which provide a qualitative increase in the effectiveness of processes aimed at finding and selecting gifted children at the initial stage of their sports improvement. The article presents the results of a pedagogical experiment with young acrobats, which shows the effectiveness of the use of acrobatics in organizational and pedagogical activities that form the skills of young athletes.